Effect of aging on the distribution of basic fibroblast growth factor immunoreactive cells in the rat hippocampus - ERCAN, FERİHA; ONAT, FİLİZ; ŞİRVANCI, SERAP (PERGAMON-ELSEVIER SCIENCE LTD, 2005)
Hippocampal formation is extremely sensitive to the aging process and appears to be one of the first regions to show structural and physiological changes with advancing age. Basic fibroblast growth factor (bFGF) plays an important role in the stimulation of mitogenesis in glial cells, the support of neuronal survival and the promotion of neurite outgrowth in vitro. In the present study, the effect of aging on the distribution of bFGF immunoreactive (bFGF-ir) cells was investigated. The protein product of bFGF was visualized immunohistochemically in the dorsal hippocampus of Wistar albino rats. bFGF-ir astrocytes in different subfields of hippocampus and neurons in CA2 field were quantified to determine whether changes in immunoreactivity were correlated with advancing age. Aging was accompanied by a decrease in bFGF-ir cell density in subfields of hippocampus. We concluded that aging was associated with a reduction in bFGF-ir cell density that may reflect a decreased expression of bFGF in the rat hippocampus. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: aging; hippocampus; basic fibroblast growth factor; immunohistochemistry; rat; BROWN-NORWAY RAT; AGED RATS; ASTROCYTES; NEURONS; BRAIN; GLUTAMATE; EXPRESSION; SURVIVAL; DEFICITS